Hiddushim : Celebrating Hebrew College's Centennial - Fishbane, Michael, 1943-; Green, Arthur; Sarna, Jonathan D. (Academic Studies Press, 2022)
A Centennial, writes Hebrew College President Rabbi Sharon Cohen Anisfeld, is an opportunity "to ask ourselves what has changed and what has endured...to articulate our aspirations for the next one hundred years." Gathering incisive essays in Jewish studies alongside powerful personal stories, Ḥiddushim celebrates a community connected to its source and brimming with spiritual and intellectual creativity as it looks toward the future.